(untitled) (Revista Apotheke, 2024)
The present research approaches the need to bring art closer to adult students, analysing the process and the results of a course in a university program for the public over 55 years old. The interest of these students in art is given in most cases because they would have wanted to study these issues in their youth. Beyond the usual proposals focused either on Art History or Art Workshops, this proposal generates a multidisciplinary experience, introducing concepts and practices such as urban derive or performance. Aspects such as visual culture or digital technologies and art education are also integrated. Research methodology is mixed, combining the Case Study with Arts-Based Research. The photographs acquire an important value as a result of the research. We value positively the benefits of lifelong learning, using participatory practices that take into account the experience and knowledge of the students. Through individual surveys and focus groups, the information is collected, which finally offers us a positive and rewarding result, as stated by the students.